The battle for Duncragglin - Vanderwal, Andrew H. (Plattsburgh, N.Y. : Tundra Books, 2009)
Twelve-year-old Alex spends the summer in Scotland with his uncle after his parents mysteriously disappear, but when he investigates the ancient ruins of a nearby castle that is rumored to be haunted, Alex is whisked into the thirteenth century during William Wallace's rebellious military campaign.
Kirkus Review.
5.9
5-8
Keywords: Wallace, William, -- Sir, -- d. 1305 -- Juvenile fiction; Wallace, William, -- Sir, -- d. 1305 -- Fiction; Wallace, William, -- Sir, -- d. 1305 -- Fiction; Castles -- Juvenile fiction; Time travel -- Juvenile fiction; Castles -- Fiction; Time travel -- Fiction; Castles -- Fiction; Time travel -- Fiction; Scotland -- History -- Wallace's Rising, 1297-1304 -- Juvenile fiction; Scotland -- History -- Wallace's Rising, 1297-1304 -- Fiction; Scotland -- History -- Fiction